Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Let’s solve the equation step by step:
[tex]\[ \frac{2x}{1 + 2y} = \frac{3x + 4i}{x - 3y} \][/tex]
First, we want to cross-multiply to eliminate the fractions:
[tex]\[ 2x(x - 3y) = (3x + 4i)(1 + 2y) \][/tex]
Now, distribute on both sides:
[tex]\[ 2x \cdot x - 2x \cdot 3y = 3x + 3x \cdot 2y + 4i + 4i \cdot 2y \][/tex]
Simplify the equation:
[tex]\[ 2x^2 - 6xy = 3x + 6xy + 4i + 8iy \][/tex]
Combine like terms and move them to one side:
[tex]\[ 2x^2 - 6xy - 3x - 6xy - 4i - 8iy = 0 \][/tex]
Group the real and imaginary parts separately:
Real part:
[tex]\[ 2x^2 - 6xy - 3x = 0 \][/tex]
Imaginary part:
[tex]\[ 0 = 4i + 8iy \][/tex]
From the imaginary part equation, we get:
[tex]\[ 4i + 8iy = 0 \][/tex]
To find [tex]\(y\)[/tex], factor out the common term [tex]\(4i\)[/tex]:
[tex]\[ 4i(1 + 2y) = 0 \][/tex]
Since [tex]\(i\)[/tex] is imaginary and non-zero:
[tex]\[ 1 + 2y = 0 \implies y = -\frac{1}{2} \][/tex]
Now, substituting [tex]\( y = -\frac{1}{2} \)[/tex] back into the real part equation:
[tex]\[ 2x^2 - 6x\left(-\frac{1}{2}\right) - 3x = 0 \][/tex]
Simplify the equation:
[tex]\[ 2x^2 + 3x - 3x = 0 \implies 2x^2 = 0 \][/tex]
So,
[tex]\[ x = 0 \][/tex]
Thus, the solution to the equation [tex]\( \frac{2 x}{1+2 y}=\frac{3 x+i 4}{x-3 y} \)[/tex] given that [tex]\(x\)[/tex] and [tex]\(y\)[/tex] are real is:
[tex]\[ (x, y) = (0, -\frac{1}{2}) \][/tex]
[tex]\[ \frac{2x}{1 + 2y} = \frac{3x + 4i}{x - 3y} \][/tex]
First, we want to cross-multiply to eliminate the fractions:
[tex]\[ 2x(x - 3y) = (3x + 4i)(1 + 2y) \][/tex]
Now, distribute on both sides:
[tex]\[ 2x \cdot x - 2x \cdot 3y = 3x + 3x \cdot 2y + 4i + 4i \cdot 2y \][/tex]
Simplify the equation:
[tex]\[ 2x^2 - 6xy = 3x + 6xy + 4i + 8iy \][/tex]
Combine like terms and move them to one side:
[tex]\[ 2x^2 - 6xy - 3x - 6xy - 4i - 8iy = 0 \][/tex]
Group the real and imaginary parts separately:
Real part:
[tex]\[ 2x^2 - 6xy - 3x = 0 \][/tex]
Imaginary part:
[tex]\[ 0 = 4i + 8iy \][/tex]
From the imaginary part equation, we get:
[tex]\[ 4i + 8iy = 0 \][/tex]
To find [tex]\(y\)[/tex], factor out the common term [tex]\(4i\)[/tex]:
[tex]\[ 4i(1 + 2y) = 0 \][/tex]
Since [tex]\(i\)[/tex] is imaginary and non-zero:
[tex]\[ 1 + 2y = 0 \implies y = -\frac{1}{2} \][/tex]
Now, substituting [tex]\( y = -\frac{1}{2} \)[/tex] back into the real part equation:
[tex]\[ 2x^2 - 6x\left(-\frac{1}{2}\right) - 3x = 0 \][/tex]
Simplify the equation:
[tex]\[ 2x^2 + 3x - 3x = 0 \implies 2x^2 = 0 \][/tex]
So,
[tex]\[ x = 0 \][/tex]
Thus, the solution to the equation [tex]\( \frac{2 x}{1+2 y}=\frac{3 x+i 4}{x-3 y} \)[/tex] given that [tex]\(x\)[/tex] and [tex]\(y\)[/tex] are real is:
[tex]\[ (x, y) = (0, -\frac{1}{2}) \][/tex]
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.